Assessment of cellular effects of nanomaterials - Báčová, Jana (Univerzita Pardubice, 2023)
Nanomaterials have been commonly used for various purposes based on their unique properties. However, nanomaterials can enter organisms due to their small size and induce biological effects in cells. In the last decade, attention has been given to studies investigating the biological effects of nanomaterials, i.e., biocompatibility or cytotoxicity. The present PhD thesis has been focused on study of biological effects of nanomaterials in vitro. Initially, we optimized the experimental conditions of TiO2 P25 nanoparticles preparation for testing in human pulmonary A549 cells. When the optimal parameters for the use of TiO2 P25 nanoparticles in A549 cells were defined, we were able to obtain reproducible results showing mild cytotoxicity of TiO2 P25 nanoparticles. We also estimated the biological effects of Al2O3, SiO2, ZrO2, TiO2, and WO3 nanoparticles in comparison to fibers of the same chemical composition. In general, our comprehensive study provided findings that inorganic fibers did not exhibit larger toxicity in A549 cells in comparison to appropriate nanoparticles. In addition, we focused on investigation of the biological effects of TiO2-based nanomaterials including aerogel TiO2 nanopowder, TiO2-based adsorbents, and sheets and nanotubes modified by Atomic Layer Deposition technique. These nanomaterials did not cause any significant damage of human cells in contrast to multiwalled carbon nanotubes. The surface modification by Atomic Layer Deposition significantly increased the biocompatibility of materials. In conclusion, the results in the present PhD thesis provide a comprehensive view on biological effects of nanomaterials in cultured cells.
Hodnocení buněčných účinků nanomateriálů
Keywords: oxid titaničitý; titanium dioxide; nanočástice; vlákna; buňky A549; depozice atomárních vrstev; nanoparticles; fibers; A549 cells; atomic layer deposition